2010
DOI: 10.1142/s0219691310003754
|View full text |Cite
|
Sign up to set email alerts
|

Denoising and Enhancement of Mammographic Images Under the Assumption of Heteroscedastic Additive Noise by an Optimal Subband Thresholding

Abstract: Mammographic images suffer from low contrast and signal dependent noise, and a very small size of tumoral signs is not easily detected, especially for an early diagnosis of breast cancer. In this context, many methods proposed in literature fail for lack of generality. In particular, too weak assumptions on the noise model, e.g., stationary normal additive noise, and an inaccurate choice of the wavelet family that is applied, can lead to an information loss, noise emphasizing, unacceptable enhancement results,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 42 publications
0
4
0
1
Order By: Relevance
“…The prime steps involved in that work are the mammogram enhancement by homomorphic filtering, detection of the region of interest by Local Seed Region Growing algorithm, feature extraction by the spherical wavelet transform and the classification of the breast masses by the classifier, Support Vector Machine. A suitable wavelet thresholding suggested by Mencattini et al [5] in connection to the discrete dyadic wavelet transform relates all the denoising and enhancement related parameters to the noise variance and cancer symptoms. The background and the foreground of the mammograms are properly segmented to facilitate the computation of contrast enhancement index.…”
Section: Introductionmentioning
confidence: 99%
“…The prime steps involved in that work are the mammogram enhancement by homomorphic filtering, detection of the region of interest by Local Seed Region Growing algorithm, feature extraction by the spherical wavelet transform and the classification of the breast masses by the classifier, Support Vector Machine. A suitable wavelet thresholding suggested by Mencattini et al [5] in connection to the discrete dyadic wavelet transform relates all the denoising and enhancement related parameters to the noise variance and cancer symptoms. The background and the foreground of the mammograms are properly segmented to facilitate the computation of contrast enhancement index.…”
Section: Introductionmentioning
confidence: 99%
“…One such work by Görgel et al [2] demonstrates the denoising of the mammograms by the wavelet transform and homomorphic filtering. Again, mammogram denoising and enhancement methodology proposed by Mencattini et al [3] is based on the optimal thresholding which relates all the denoising and contrast enhancement parameters to the noise variance and the extent of cancer signs. A recent investigation [4] developed on the spherical wavelet transform for feature extraction and Local Seed Region Growing algorithm for region of interest identification describes the detection and classification of suspect breast masses as benign and malignant.…”
Section: Introductionmentioning
confidence: 99%
“…In order to achieve shift invariance, researchers have proposed the undecimated DWT (UDWT) [ 8 10 ]. Mencattini et al reported a UDWT-based method for the reduction of noise in mammographic images [ 11 ]. The reported method was robust and effective.…”
Section: Introductionmentioning
confidence: 99%